Islam dinamis : menegakkan nilai-nilai ajaran al-Qur'an dalam kehidupan modern di Indonesia - Harahap, Syahrin (Yogyakarta : Tiara Wacana Yogya, 1997)
Islam and interpretation of the Koran in Indonesian modern society; collected articles
Includes bibliographical references (p. 301-312) and index
Keywords: Koran -- Criticism, interpretation, etc; Islam -- Indonesia -- 20th century